2017
DOI: 10.1002/ecy.1909
|View full text |Cite
|
Sign up to set email alerts
|

High and variable mortality of leatherback turtles reveal possible anthropogenic impacts

Abstract: The number of nesting leatherback turtles (Dermochelys coriacea) in the eastern Pacific Ocean has declined dramatically since the late 1980s. This decline has been attributed to egg poaching and interactions with fisheries. However, it is not clear how much of the decline should also be ascribed to variability in the physical characteristics of the ocean. We used data on individually marked turtles that nest at Playa Grande, Costa Rica, to address whether climatic variability affects survival and inter-breedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Moreover, Gomerčić et al in 2009 reported for the first time that ingestion of gill-net parts leads to larynx strangulation [3]. Similar considerations are reported also for sea turtles [18,19].…”
Section: Accepted Manuscript Introductionsupporting
confidence: 67%
“…Moreover, Gomerčić et al in 2009 reported for the first time that ingestion of gill-net parts leads to larynx strangulation [3]. Similar considerations are reported also for sea turtles [18,19].…”
Section: Accepted Manuscript Introductionsupporting
confidence: 67%
“…Adult survival was critically low in both subpopulations (annual survival probabilities for México = 0.705 [CI: 0.675-0.741] and Costa Rica = 0.778 [CI: 0.750-0.807]). To ensure population stability in long-lived species such as turtles, adult survival is generally 0.90 or higher 56,57 with low variability over time 58 . Indeed, previous estimates of adult survival rates of nesting leatherback females have been ≥0.89 for nesting populations that were stable or increasing at the time of study [38][39][40] .…”
Section: Resultsmentioning
confidence: 99%
“…The addition of the predictions from this model to the South Pacific TurtleWatch publicly available website (https://www.upwell.org/sptw) will be combined with a communication strategy across different platforms (e.g., mobile, web, printed, radio) aimed at disseminating information to an array of different stakeholders, such as government agencies, the fishing community, and the broader public. Increased protection for this population at sea should be a high priority for this long-lived animal that is rapidly declining as a result of human activity (Santidri an Tomillo et al, 2017)…”
Section: Covariatementioning
confidence: 99%